Pre-pregnancy body mass index and breastfeeding initiation, early cessation and longevity: evidence from the first wave of the UK Millennium Cohort Study. Issue 12 (10th September 2018) - Campbell, Tammy; Shackleton, Nichola
Abstract : Background: International evidence indicates relationships between pre-pregnancy body mass index (BMI) and breastfeeding behaviours. This study aims to assess associations between key points in the breastfeeding trajectory (initiation, early cessation and longevity) and pre-pregnancy BMI in a recent, nationally representative British cohort. It also aims to explore in the British context potential moderation by mothers' ethnic group. Methods: The sample comprises 17 113 mothers from the UK Millennium Cohort Study who have information on pre-pregnancy BMI. Associations between pre-pregnancy BMI categories and breastfeeding initiation, early cessation and longevity are tested using logistic regression. Directed acyclic graphics identify appropriate minimal adjustment to block biasing pathways and classify total and direct effects. Results: After adjusting for confounders, there are large differences in breastfeeding early cessation and longevity by pre-pregnancy BMI group. Differences in propensity to initiation are negligible. Having begun breastfeeding, overweight and obese mothers are more likely to cease in the first week and less likely to continue past 4 months. Observed potential mediators within pregnancy and delivery provide little explanation for relationships. Evidence for moderation by ethnicity is scant. Conclusions: The causal mechanisms underlying relationships between pre-pregnancy overweight, obesity, and breastfeeding behaviours require further research. However, this study suggests pre-pregnancy BMI as one predictive measure for targeting support to women less likely to establish breastfeeding in the early days, and to continue beyond 4 months. The nature of support should carefully be considered and developed, with mind to both intended and potential unintended consequences of intervention given the need for additional investigation into the causes of associations.